THE OPTIMIZATION OF EMPLOYEE PERFORMANCE IMPROVEMENT REVIEWED FROM THE PERSPECTIVES OF PERFORMANCE ALLOWANCES, WORK MOTIVATION, AND WORK DISCIPLINE IN THE LPD BANYUNING, LPD LUMBANAN, LPD PADANG BULIA, LPD SARI MEKAR - Ningsih, Luh Kartika; Prastiwi, Ni Luh Putu Eka Yudi; Gorda, AAN Eddy Supriyadinata (Journal of Business on Hospitality and Tourism, 2020)
The purpose of this study was to find out how to Improve Employee Performance reviewed from the Perspectives of Performance Allowances, Work Motivation, and Work Discipline in the LPD Banyuning, LPD Lumbanan, LPD Padang Bulia, LPD Sari Mekar. This study used a quantitative approach. The data analysis technique used in the structural equation model (Structural Equation Modeling-SEM) was based on variance or component based SEM, which is famously called Partial Least Square (PLS) Visual version 3.0. All relationships examined showed positive and significant results. For this reason, in its realization, the LPD Banyuning, LPD Lumbanan, LPD Padang Bulia, LPD Sari Mekar were expected to be able to improve the performance of the Employees with the Performance Allowances. The realization of employee performance, this is also the impact of the existence of Work Motivation, Performance Allowances, and Work Discipline that will have an impact on improving employee performance in the LPD Banyuning, LPD Lumbanan, LPD Padang Bulia, LPD Sari Mekar.